Variables Determining Muzakki Loyalty in Paying Zakat (Equilibrium: Jurnal Ekonomi Syariah, 2023)
This study aims to assess whether accountability, transparency, service quality, satisfaction, and religiosity affect Muzakki's loyalty with trust as Muzakki's intervening variable. This type of research is explanatory research and uses the survey method. The data collection technique used was a questionnaire containing written questions answered by respondents, namely Muzakki's (payer of zakat, infaq and sadaqah) at amil zakat institutions. This research surveys 100 respondents (muzakki) in Lembaga Amil Zakat, Infaq dan Sedekah Muhammadiyah (Lazismu) Central Java. The sampling technique used purposive sampling, which set the samples based on criteria. The data were analysed using partial least square-structural equation modelling (PLS-SEM), which was then processed using the SmartPLS application. The results of this study indicate that the muzakki loyalty to zakat management organizations (Lazismu) will increase in paying zakat by increasing muzakki's trust through satisfaction, service quality, religiosity, transparency and accountability in accordance with PSAK 109.